Understanding your users : a practical guide to user requirements methods, tools, and techniques - Courage, Catherine (Morgan Kaufmann series in interactive technologies., 2005)
Today many companies are employing a user-centered design (UCD) process, but for most companies, usability begins and ends with the usability test. Although usability testing is a critical part of an effective user-centered life cycle, it is only one component of the UCD process. This book is focused on the requirements gathering stage, which often receives less attention than usability testing, but is equally as important. Understanding user requirements is critical to the development of a successful product. Understanding Your Users is an easy to read, easy to implement, how-to g.